(untitled) (Research, Society and Development, 2021)
The aim of the present study was to investigate the influence of increased SCC on the expression of milk proteins through the use of analyzes microfluid electrophoresis (lab-on-a-chip). Fifty samples of cow’s milk from two properties located in State of Goiás were analyzed. Samples were analyzed for somatic cell counts and lab-on-a-chip microfluidic electrophoresis. For the correlation test between the protein profile and the SCC the samples were stratified into five groups of Scores of Somatic Cell. A completely randomized design with five treatments was used, data were analyzed using descriptive statistics and graphical representations. There was a significant increase in the concentration of the protein component when compaired SSC 1 and 3, 1 to 4 and 1 and 5. It was also possible to observe a statistical difference in the results of the Lactose component when comparing SSC 1 and 3 and 3 and 4. In the descriptive evaluation of the variable "Concentration" of the milk proteins it was possible to observe differences in the concentration values as a function of SSC. It was possible to observe statistical difference for the results obtained for α-LA, when compared to ECS 1,2 and 3 and ECS 5; For IgG, samples from SSC 4 and 5 showed different concentrations of samples from SSC 1,2 and 3; and the LF protein, presented different results between the samples of SSC 1 and 5. We concluded that high abundance whey proteins have their concentration decreased with the occurence of the mastitis; Defense proteins such as Lactoferrin, Lactoperoxidase, IgG and IgM have their concentration increased when comparing milk samples from cows with subclinical mastitis and milk samples from healthy cows; Lactoferrin and IgG proteins are potential targets for identifying cows with subclinical mastitis in milk samples and may be considered biomarkers.